Management of Character Education Curriculum in Islamic Boarding School - Thoyyibin; Ali Shah, Syed Ahmad; Khamim, Nur (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2023)
This article aims to describe the planning, organization, and evaluation of the character education curriculum at the Al Furqon Islamic Boarding School, Kota Baru Driyorejo Gresik. This article has used a qualitative research method with a case study approach. The data collection techniques are interviews, documentation, and observation. Observations were made by participating in observations. While the informants of this study were the head of the pesantren, caregivers, and several Ustadz (boarding school administrators). Data analysis techniques follow this model of Huberman. The result of this article is that the planning carried out at the Al Furqon Islamic Boarding School is neatly arranged and agreed upon by the leadership and the Foundation. Implementation of the agreed curriculum is carried out with the commitment of all pesantren stakeholders. Evaluation is used as a control of the implementation of whether or not the target has been achieved.